Immersive Place-Based Attachments in Rural Australia: An Overview of an Allied Health Program and Its Outcomes - Leanne J. Brown; Luke Wakely; Alexandra Little; Susan Heaney; Emma Cooper; Katrina Wakely; Jennifer May; Julie M. Burrows (MDPI AG, 2022)
This paper describes a rural immersive attachment program for allied health students at an Australian University Department of Rural Health and its workforce outcomes. A mixed methods longitudinal cohort study, with data collected via end-of-placement and post-graduation surveys. Over 13 years, 311 allied health 'year-long' immersive rural attachments, as well as short-term placements, were supported. Pre- and post-placement rural practice intention ratings were paired (from 572 end of placement surveys) for 553 (96.7%) students. Students from metropolitan (49.4%, n = 273, p < 0.001), and rural origin (50.6%, n = 280, p < 0.001) showed a significant increase in rural practice intention. At 1 year post-graduation, 40.3% (n = 145) of graduates had worked in a rural or remote location in Australia, 39.9% at 3 years (n = 87) and 36.5% (n = 42) at 5 years. Longer-term rural attachments were found to be associated with rural practice location, independent of rural background. Those who had undertaken a longer rural attachment (≥18-weeks) were twice as likely to be working in a rural or remote area than those <18 weeks at 1 year (OR 2.018 95% CI 1.204-3.382) and 2.7 times as likely at 3 years (OR 2.727, 95% CI (1.325-5.614). Supporting students to undertake rural immersive attachments appears to be associated with greater rural practice intention and later rural practice.